ANALISIS YURIDIS OBJEK JAMINAN DEBITUR YANG DILELANG TANPA MELALUI KEBIJAKAN RESTRUKTURISASI OLEH BANK RAKYAT INDONESIA (STUDI PUTUSAN NOMOR 486/PDT/2021/PT SMG): Yuridis Analysis the Object of The Garanties of Debitures Without Passing the Restructuring Provisions of Bank Rakyat Indonesia (Study Decision Number 486/Pdt/2021/Pt Smg) - Syaharani, Claudia; Santoso, Rahmat (Faculty of Law, Universitas Trisakti, 2025)
Rescheduling is a legal strategy offered by financial institutions like banks to aid debtors struggling with debt by adjusting certain terms of their credit agreements, such as payment schedules and loan amounts. However, when banks auction off collateral without adhering to their rescheduling policies, as discussed in high court case No.486/PDT/2021/PT SMG concerning property rights disputes involving guarantees for debt settlement, significant legal consequences arise for debtors of Bank Rakyat Indonesia. This study employs normative legal research using secondary data and employs descriptive qualitative analysis. It concludes that unilateral auctioning of secured assets by the bank, without considering debtor interests via rescheduling, can lead to debtor losses, particularly in terms of forfeiting ownership of guaranteed assets.